2010
DOI: 10.1007/s12028-010-9473-8
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Procedures for Evacuation of Intracerebral Hemorrhage Reduces Perihematomal Glutamate Content, Blood–Brain Barrier Permeability and Brain Edema in Rabbits

Abstract: Minimally invasive surgery for removal of an intracerebral hematoma could significantly reduce the glutamate content, BBB permeability and the brain water content in perihematomal brain tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 26 publications
(31 reference statements)
0
31
0
Order By: Relevance
“…There is evidence from porcine (Wagner et al, 1999) and rabbit (Wu et al, 2011a) ICH models of decreased tissue injury, BBB opening, and edema and hematoma volumes through minimally invasive clot aspiration and thrombolysis. A recent clinical randomized controlled trial showed benefits of stereotactic evacuation over conventional craniotomy in terms of functional outcomes and postoperative complications (Zhou et al, 2011), and a further randomized clinical trial (the Minimally Invasive Surgery plus Tissue Plasminogen Activator for Intracerebral Hemorrhage Evacuation, MISTIE trial) is currently ongoing.…”
Section: Clot Removalmentioning
confidence: 99%
“…There is evidence from porcine (Wagner et al, 1999) and rabbit (Wu et al, 2011a) ICH models of decreased tissue injury, BBB opening, and edema and hematoma volumes through minimally invasive clot aspiration and thrombolysis. A recent clinical randomized controlled trial showed benefits of stereotactic evacuation over conventional craniotomy in terms of functional outcomes and postoperative complications (Zhou et al, 2011), and a further randomized clinical trial (the Minimally Invasive Surgery plus Tissue Plasminogen Activator for Intracerebral Hemorrhage Evacuation, MISTIE trial) is currently ongoing.…”
Section: Clot Removalmentioning
confidence: 99%
“…In recent years, the minimally invasive surgery has been emerging as an alternative for craniotomy due to its improved survival rate and reduced complication rate [32]. Several clinical and experimental studies have demonstrated minimally invasive techniques to be effective for the treatment of ICH [29,30,32]. However, although MIS can alleviate the hematoma to a large extent by reducing its physical size and the release of neurotoxic substances, it cannot remove the erythrocytes and cytotoxic substances that extravasate into the brain adjacent to the hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used in this study were same to those in our previously published studies [29,30]. Briefly, the rabbits were anesthetized by injecting 20% urethane (2ml/kg) into the marginal ear vein.…”
Section: Ich Model Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the increase in BBBP was sustained for up to 14 days [36]. One animal study found that the measurements of the BBBP were similar between 1 week and 1-day post-ICH [40].…”
Section: Application In Hemorrhagic Strokementioning
confidence: 99%